STRATEGI PRESERVASI PENGETAHUAN TRADISIONAL MINANGKABAU MELALUI DIGITALISASI TRADISI LISAN DI PERPUSTAKAAN PERGURUAN TINGGI - Amini, Aisyah; Zalmi, Fadhila Nurul Husna (UIN Imam Bonjol Padang, 2025)
Traditional Minangkabau knowledge—such as pepatah-petitih (proverbs), kaba (epic tales), and traditional pantun— represents a cultural heritage that has long been transmitted orally across generations. However, modernization, shifting lifestyles, and the weakening of customary practices have placed this knowledge at risk of extinction. University libraries hold a strategic role as knowledge management institutions in adopting digital technology to document and preserve oral traditions. This article aims to answer the question: what strategies can be applied by university libraries to preserve traditional Minangkabau knowledge through the digitization of oral traditions? This study employs a descriptive qualitative approach using a case study method at Islamic university libraries in West Sumatra. Data collection techniques include interviews with librarians, observation of documentation activities, and analysis of policy documents and local digital cultural content. The findings reveal that effective strategies involve collaboration among librarians, lecturers, students, and local community members. Digitization activities are carried out through oral narrative collection, audio-visual recording, metadata management, and publication via institutional repositories and open-access digital platforms. Challenges encountered include limited technology, lack of documentation standards, and ethical concerns related to cultural publication. The study concludes that digitizing oral traditions can be an effective strategy for knowledge preservation when supported by institutional policies, digital-cultural literacy training, and collaboration among stakeholders. University libraries serve not only as knowledge repositories but also as facilitators of local cultural preservation within the digital ecosystem.